From Deficit to Diversity: Inviting learners to use their linguistic and cultural repertoires for Literacy Learning - Runciman, Talya (School of Education, 2019)
This study explores how teaching strategies that constructively employ learners’ linguistic and cultural resources can enhance their learning and participation in literacy lessons. In South Africa, as elsewhere in the world, language policies tend to favour English as the sole medium of instruction and oppose multilingual teaching (Creese and Blackledge, 2010; McKinney, 2017). However, these linguistic restrictions on teaching are hugely problematic for the majority of South African learners who do not have access to dominant language and cultural practices. This study draws on sociocultural theory in that it views language use in the classroom to have a social context, where language regimes at play in greater society determine the language ideologies of teaching and learning in the classroom (Makoe and McKinney, 2014). In addition, this study draws on recent research that advocates multilingual teaching strategies such as translanguaging and translation (Gardia and Sylvan, 2011; McKinney, 2017; Probyn, 2006), as well as drawing on learners’ cultural repertoires and the use of multimodal activities (Newfield, 2011; Stein and Newfield, 2006). The data discussed in this study is drawn from a teaching intervention with Grade 1 and 2 learners that was implemented in a South African primary school. This intervention primarily focused on inviting learners to use their linguistic and cultural repertoires during after-school literacy lessons. Using a linguistic ethnographic approach (Copland and Crease, 2015), this qualitative study describes and analyses the benefits of using such teaching methodologies. This study shows how using learners’ full linguistic and cultural repertoires and multimodal interactions is beneficial to their learning.